Green architecture environmentally friendly housing - Films For The Humanities & Sciences (Firm); Shopware (Firm) (hamilton, New Jersey : Films for the Humanities & Sciences, 2008)
Combining aesthetics, sustainability, and function is the challenge of green architecture -- and 20 teams of college students from North America and Europe brilliantly rise to that challenge as they compete to design, build, and demonstrate the operation of the most attractive and energy-efficient house at the 2007 Solar Decathlon held in Washington, D.C. This program tracks the teams from the University of Maryland, MIT, The University of Texas at Austin, and Lawrence Technological University as they seek out corporate sponsors, research available materials, and hone their construction skills to create appealing living spaces that require zero energy
Title from title screen
DVD format
Keywords: Solar houses -- Design and construction; Architecture and energy conservation; Dwellings -- Environmental engineering; Sustainable architecture; Architecture, Domestic